Peran Pendidikan Agama Islam terhadap Akhlakul Karimah Anak - Eri Subaeri Ahmad (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2020)
This study aims to explore the concept of morality and Muslim personality according to the book of Akhlak Li Al-Banin. The research uses a qualitative approach with a literature study approach. The results of the document analysis show that: 1) morals of karimah include several aspects starting from morals towards Allah, morals towards the Prophet Muhammad SAW, morals towards mothers, morals towards fathers, morals towards sisters, morality towards brothers, morals towards relatives, towards assistants, morals towards people who hurt him, morals towards neighbors, morals towards teachers, and morals towards friends. 2) The factors forming the Muslim personality are internal and external factors (education), nature, taufik and guidance. 3) The Muslim personality has special characteristics both in relation to God (morals to God), relationships to apostles (morals to apostles) and relationships with fellow humans (morals to fellow humans). Akhlakul karimah is an implication for the formation of a Muslim personality who is obedient to Allah, the Apostle, and family. It is recommended that moral education in children should start early, before the character and personality of a child who is still holy is colored by environmental influences that are not necessarily parallel to religious guidance; 2) Everyone must equip himself with the Muslim personality, both through formal and non-formal education.